Taperekue ou abandonner sa demeure. Une population rurale guaranophone du Paraguay - Capucine Boidin (Journal de la Société des Américanistes)
Taperekue or abandoned houses among rural and guarani speaking population of Paraguay. Since 1940, the important mobility of the rural population in Paraguay struck investigators, for it contrasts with the traditional image of rooted communities rural villages are supposed to be. Some ethnologists asked if it would not be there a survival of tupi-guarani nomadism, without trying to answer. Our observations propose to think mobility of these people within their general relation with their dwelling in their everyday life and with the general problem of interbreeding. It appears that the abandonment of houses is linked with funeral rituals: houses seem to be lived as transitional places. Past is not to be remembered but to be erased in order to enable spatial regeneration.